The Influence of Nutrient (N and P) Enrichment and Ratios on Phytoplankton Abundance in Keunekai Waters, WehIsland, Indonesia - Wisha, Ulung Jantama; Ondara, Koko; Ilham, Ilham (Makara Journal of Science, 2018)
The Keunekai waters around Weh Island, Indonesia, have become a prone coastal area because of degradation from climate anomalies and anthropogenic pressure. The high level of coral mortality caused by mass bleaching and fish bombing several years ago may have led to the deterioration of the water conditions and the disruption of the biogeo-chemical cycle, resulting in potential nutrient enrichment and algae blooms (eutrophication). This study aimed to de-termine the influence of nutrient ratios on phytoplankton abundance and monitor the existing waterconditions aroundKeunekai. Spectrophotometry analysis was used to determine the concentrations of the nutrients, and the Sedgewick-Rafter counting method was used to identify the species and abundance of the phytoplankton. A large variation in N content (ranging from 1.1 to 1.6 mg N/L) and, particularly, P content (ranging from 0.02 to 0.18 mg P/L) most likely reflected differences in the supply ratios of N and P, rather than differences in absolute N and P availability. Three taxa of phytoplankton and their relative abundance were identified in the study area: Bacillariophyceae (diatom) (72%), Cyanophyceae (3%), and Dinoflagellate (25%). It was found that P-limitation mostly controls potential algae blooms, which support the density of Dinoflagellates thatmay endanger the water.